Protective effect of phillyrin against cerebral ischemia/reperfusion injury in rats and oxidative stress-induced cell apoptosis and autophagy in neurons. Issue 3 (1st March 2022) - Chen, Shu; Zhang, Shan; Wu, Honggang; Zhang, Daobao; You, Guoliang; You, Jing; Zheng, Niandong
ABSTRACT: This study explored the role and potential molecular mechanism of phillyrin in cerebral ischemia/reperfusion (I/R) injury. The rat middle cerebral artery occlusion (MCAO)/R model was constructed, and cerebral infarction volume, brain water content, and neurological score were measured. Neuron morphological structures in brain tissues and primary neuron apoptosis were detected using hematoxylin and eosin (H&E) staining and Hoechst 33258 staining, respectively. In MCAO/R rats, phillyrin markedly reduced cerebral infarction volume, neurological score, and brain water content and inhibited neuron apoptosis. In vitro experiments showed that phillyrin remarkably increased viability and decreased lactate dehydrogenase (LDH) release of H2 O2 -injured neurons. Moreover, phillyrin remarkably downregulated the proportion of apoptosis-related protein B-associated X (Bax)/B-cell lymphoma protein 2 (Bcl-2) and reduced procaspase-3, phospho-Akt (p-Akt-1), and phosphorylation-mammalian target of rapamycin (p-mTOR) levels in H2 O2 -injured neurons. Furthermore, phosphatidylinositol-3 kinase (PI3K) inhibitor ZSTK474 weakened the effects of phillyrin on p-mTOR, p-Akt-1, characteristic proteins of autophagy 3-II (LC3-II) and beclin-1 levels, and H2 O2 -induced neuronal apoptosis and autophagy. Taken together, phillyrin alleviates I/R injury by inhibiting neuronal cell apoptosis and autophagy pathway, which may provide a new treatment strategy for cerebral I/R injury. Graphical Abstract: uf0001